Analysis and investigation of a novel microwave sensor with high Q-factor for liquid characterization - Ammar Alhegazi; Zahriladha Zakaria; Noor Azwan Shairi; Tole Sutikno; Rammah A. Alahnomi; Ahmed Ismail Abu-Khadrah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper, a new design of microwave sensor with high Q-factor for liquid characterization is analyzed and investigated. The new microwave sensor is based on a gap waveguide cavity resonator (GWCR). The GWCR consists of upper plate, lower plate and array of pins on the lower plate. The liquid under test (LUT) is characterized by placing it inside the GWCR where the electric field concentrates using a quartz capillary that is passing through microfluidic channels. The results show that the proposed sensor has a high Q-factor of 4832. Moreover, the proposed sensor has the ability to characterize different types of liquids such as oils, ethanol, methanol and distilled water. The polynomial fitting method is used to extract the equation of the unknown permittivity of the LUT. The results show that the evaluated permittivity using the proposed sensor has a good agreement with the reference permittivity. Therefore, the proposed sensor is a good candidate for food and pharmaceutical applications.